Keselesaan bermukim di Flat : Kajian kes persepsi masyarakat terhadap Rumah Susun Sukaramai, Medan, Indonesia / Fashbir Noor Sidin - Fashbir , Noor Sidin (1999)
In Indonesia, development of flat (rumah susun) has started ten years ago as a model project among major cities likes Jakarta, Surabaya, Medan, Bandung and Palembang. A: Jakarta, low-cost flat is 'favourable' and 'moderate' at Medan and Bandung while 'unfavourable' at Surabaya and Pelembang. Up to now, the demand for flat still high at Jakarta and also at Surabaya related to growth of urbanization. Flat which is located at city centre is more favourable to fixed and low-income groups because of the influence of the cost of living including transportation expenditures. In Medan City, Rumah Susun Sukaramai, are currenty occupied mostly by the Chinese especially in historical area such as the the Chinese Area. The study on rumah susun tries to find out the level of living satisfaction among occupants in many aspects including physical and social environments. This study also tries to find some preferences among occupants in choosing rumah susun as new residential area compared to their former residence This study assumes that rumah susun is favourable for city resident and its comfortability depend on adjustment attitude and behavior of the residents toward equilibrium conditions. This study was conducted in three parts. The fisrt part is to formulate any aspects to be developed as indicators of comfortability likes facility, amenity, and security. The second part of the study focused on three major factors of living at rumah susun: physical-technical, socio-economic and socio-cultural factors. Method were used stratified random and proporsional technique for both studies with 200 respondents. The third part of the study uses population respondents was divided into three groups as their class of residence . It means, this categorization point to the status of socio-economic of responden. These results of study is useful for many sectors which is related to housing i.e. developer or govermment. There are two approaches in this study. First, the analysis on the aspect of interaction among residents and with their physical and social environment. Human ecological approach analyses the relationship between human factors and physical-social environments. In the psycho-social approach, analyses on the perception and feedback of respondents related to their living comfortability. Both approaches highlight$ the social equilibrium which is based on family happiness and community harmony as important factors for sustainable community development. This study found out that respondents are satisfy with rumah susun even they want to live in better rumah susun in the future. In spite of some complaints to the physical and social aspects, majority of the are owners who do not prevent them to live there. Neighborhood interaction is satisfy especially in some aspects that equal in needs i.e. take care of children. They also confessed that rumah susun are relatively better than their former house. Majority of the respondents are young with little family size and formerly live with parents or rent a house in city centre area. Their views on housing management by resident association are clear and they felt that it was not satisfactory. In general. there are many options related to their class of resident. This study tries to point out to the need of housing for everybody and rumah susun is an appropriate option especially rental flats in handling the lack of housing supply to the city residents. The dimensions of human and society are very important to ensure they live comfortability through 'mesra jiran' or loving neighborhood and awarenees of social responsibility. The equilibrium of society is tied to this community and it's influence on the future of rumah susun including its physical environment i.e. social facilities is greatly appreciated.